2020
DOI: 10.3390/agronomy10040501
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Nutraceutical and Sensory Traits of Six Papaya (Carica papaya L.) Cultivars Grown in Greenhouse Conditions in the Mediterranean Climate

Abstract: Six papaya (Carica papaya L.) cultivars, grown in a Mediterranean climate under greenhouse conditions, were screened for physicochemical properties, antioxidant capacity, nutritional and sensory characteristics. The fruits, harvested with more than 50% of yellow surface (between 60% and 77%) were tested for carotenoids content, phenolic content, reducing activity (ABTS) and cellular antioxidant activity (CAA50). The physicochemical traits were measured in terms of the titratable acidity and soluble content whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
1
19
2
1
Order By: Relevance
“…Our results, in agreement with other literature data, demonstrated that cherimoya is a tropical fruit with high nutritional value. Indeed, it had low fat content, while containing an amount of sugars and proteins generally higher than other common tropical fruits, including mango [ 7 ], kiwi [ 45 ], pineapple [ 46 ], and papaya [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, in agreement with other literature data, demonstrated that cherimoya is a tropical fruit with high nutritional value. Indeed, it had low fat content, while containing an amount of sugars and proteins generally higher than other common tropical fruits, including mango [ 7 ], kiwi [ 45 ], pineapple [ 46 ], and papaya [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, Spain is the most important producer of cherimoya fruits, and the most important cultivars are Campas and Fino de Jete , which are also the most widespread cultivars in the global market. In Italy, A. cherimola is well adapted to the pedoclimatic conditions of the tyrrhenian coastal areas of Sicily and Calabria, where there are good climate conditions for the production of other exotic and tropical fruits, such as loquat, mango, litchi, avocado, banana and papaya [ 7 , 8 , 9 , 10 ]. In particular, in Sicily, in addition to affirmed cultivars such as Fino de Jete , local ecotypes are also cultivated with very limited diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The total content of sugars was determined as previously described [ 8 ]. Briefly, the fresh tomatoes were pulped and homogenized, and the resulting juices were vortexed (4000× g , 4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…In order to quantify the protein content in tomatoes, we employed the Kjeldahl method as previously described [ 8 , 29 ]. Briefly, 1 gram of dried tomato sample was accurately weighed and then digested at 420 °C for 1 h with 10 mL of H 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation